Career Paths: Medical: student's book : 3 books - Evans, V. Virginia (Career paths, 2021)
Career Paths: Medical is a new educational source for medical professionals who want to improve their English communication in a work environment. Incorporating career-specific vocabulary and contexts, each unit offers step-by-step instruction that immerses students in the four key language components: reading, listening, speaking and writing. Career Paths English: Medical addresses topics including hospital employees, parts of the body, patient care, common illnesses and career options. The series is organized into three levels of difficulty and offers a minimum of 400 vocabulary terms and phrases. Every unit includes a test of reading comprehension, vocabulary and listening skills and leads students through written and oral production.